Identity of mating types of Phytophthora infestans in cultures from potato and tomato - S.S. SOKHI, P.S. SEKHON and (Indian Phytopathology, 2002)
A total number of 45 isolates of P. infestans, collected from potatoes in the Indian Punjab, India, were paired with a known A2 tester mating type on V8 juice agar medium. These were categorised as A1 or A2 mating type on the basis of oospore formation. Three isolates were identified as A2 and 42 as A1 mating type. A2 cultures were found to be self-sterile. A1 types differed from each other in the time taken for initiation of the anthredium and oogonium. The density of oospores was also variable when A1 isolates were paired with the A2 tester isolate. A1 and A2 types were more pathogenic on leaves of potato (cv. Kufri Chandramukhi) and tomato (cvs. Punjab Chhuhara and Punjab Kesri) compared with potato slices, however, both types did not differ in their pathogenic potential on susceptible hosts.